2021
DOI: 10.1167/iovs.62.9.24
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Control and Thyroid-Associated Orbitopathy (TAO) Orbital Fat and TAO Orbital Fibroblasts Undergoing Adipogenesis

Abstract: PURPOSE.Orbital fat hyperplasia commonly occurs in thyroid-associated orbitopathy (TAO). To understand molecular mechanisms underlying orbital adipogenesis, we used transcriptomics to compare gene expression in controls and patients with TAO, as well as in orbital fibroblasts (OFs) undergoing adipogenic differentiation. METHODS.We performed bulk RNA sequencing (RNA-Seq) on intraconal orbital fat from controls and patients with TAO. We treated cultured OFs derived from patients with TAO with adipogenic media to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…Matrix files generated from the Cellranger run were used for subsequent analysis as described previously (18, 23). Briefly, Seurat V3 (24) was used to perform downstream analysis, only including cells with more than 500 genes, and 1000 UMI, to process control and treated samples separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix files generated from the Cellranger run were used for subsequent analysis as described previously (18, 23). Briefly, Seurat V3 (24) was used to perform downstream analysis, only including cells with more than 500 genes, and 1000 UMI, to process control and treated samples separately.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, teprotumumab blocks the induction of inflammatory cytokines interleukin 6 (IL-6), and IL-8 in orbital fibroblasts (17). Single nucleus RNA sequencing (snRNA-Seq) has identified that during the early stages of adipogenesis, orbital fibroblasts upregulate the expression of both IGF-1 and IGF-1R in vitro (18).…”
Section: Introductionmentioning
confidence: 99%
“…Signalling pathways, including those for cAMP, PI3K-AKT, AGE-RAGE, lipolysis regulation, and thyroid hormone, are enriched in orbital fat isolated from patients with GO. The IGF-1R and Wnt signalling pathways appear to be enriched early in adipogenesis ( 36 ), and Wnt signalling inhibits adipogenesis in GO-OFs ( 37 ). PI3K can be activated by TSH, IGF-1, or multiple cytokine receptors, resulting in AKT activation.…”
Section: Target Cells Of Gomentioning
confidence: 99%
“…Previous studies investigated transcriptomic profiling of TAO orbit fat from orbital fibroblasts undergoing adipogenesis or adipose-derived stem cells [ 4 , 14 ]. By using next generation RNA sequencing technology, transcriptome analysis of orbital adipose tissue in active TAO was conducted [ 15 ]; however, the study did not involve the inactive ones.…”
mentioning
confidence: 99%
“…Even after eliminating the influence of inflammatory factors in the vitro experiment, the expression of Wnt signaling pathway components was significantly suppressed in OASCs [ 4 ]. During adipogenesis, WNT5A was overexpressed only during the early stage and the expression gradually decreases during the differentiation process [ 14 ]. Consistent with the results of previous studies, downregulation of WNT and WNT4 expression was observed in TAO, even in patients who had received anti-inflammatory therapies.…”
mentioning
confidence: 99%